BAHASA SASTRA LISAN MODERN TELEVISI STAND UP COMEDY: KAJIAN BUDAYA POPULER (Jurnal Bahasa Lingua Scientia, 2017)
Some television shows have presented comedy shows as one of the favorite shows. One kind of the popular comedy show is stand-up comedy. Stand-up comedy is spontaneous oral humor of which topic and content have been prepared before the performance. There are not many studies investigating the stand-up comedy from the perspective of the popular culture. This article is trying to investigate and analyze the Indonesian stand-up comedies which are performed in television. The finding shows that the modern and popular cultural aspects have added to the performance of the stand-up comedy so that more-more spectators are interested to enjoy the stand-comedy show in television.
Keywords: Stand-up comedy; oral story; modern culture